1986
DOI: 10.1300/j013v11n02_02
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Health Services by Mexican Immigrant Women in San Diego

Abstract: ABSTRACT. The limited empirical data available on maternal health problems among Mexican immigrant women in the United States suggest that they undcrutilize health services, especially general preventive care. Research conducted among legal and undocumented women in the Mexican immigrant population in San Diego, California, support these findings. Among undocumented mothers, 11.5% of their births in the U.S. occurred with no prenatal care or care sought in the third trimester, which is much higher than Mexican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 6 publications
1
32
0
Order By: Relevance
“…Noncitizens are a heterogeneous group with diverse sociodemographic characteristics and health services use rates. [39][40][41][42][43][44] In the case of California, groups such as refugees and undocumented immigrants constitute an important proportion of noncitizen immigrants and their cancer screening rates may influence those of noncitizens in general. 43 Refugees and undocumented immigrants may be disproportionately affected by cultural, knowledge, and attitudinal barriers to cancer screening, such as fatalism, fear, and lack of knowledge of preventive health interventions or their benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Noncitizens are a heterogeneous group with diverse sociodemographic characteristics and health services use rates. [39][40][41][42][43][44] In the case of California, groups such as refugees and undocumented immigrants constitute an important proportion of noncitizen immigrants and their cancer screening rates may influence those of noncitizens in general. 43 Refugees and undocumented immigrants may be disproportionately affected by cultural, knowledge, and attitudinal barriers to cancer screening, such as fatalism, fear, and lack of knowledge of preventive health interventions or their benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Mexican undocumented immigrant families underutilize health services (Cornelius et al, 1982;Chavez et aL, 1986;Rumbaut et al, 1988), yet I found that many families in my study had received medical services on credit. Undocumented immigrants do not qualify for Medi-Cal coverage, except for emergency and pregnancy services, and most do not have medical insurance, so purchasing on credit is an important alternative.…”
Section: Credit and Installment Purchasesmentioning
confidence: 66%
“…While a flurry of publications on the topic of Mexican immigrant settlement appeared in the 1980s and the early 1990s (Browning and Rodriguez, 1985;Chavez, 1986;Chavez et al, 1990;Cornelius, 1987Cornelius, , 1992Massey, 1986;Rouse, 1992;Villar, 1990), the ways people make settlement happen has not received much attention in the literature, largely because of the paucity of ethnographic research conducted in Mexican immigrant settlement communities in the U.S. In this article I ask not why such settlement has occurred-a question that can be answered at the macro-structural level of analysis by examining global economic changes (Massey et al, 1987;Cornelius, 1989) --but rather, how the process of settlement is constructed.…”
mentioning
confidence: 99%
“…Studies consistently show that immigrant women, particularly those from Asia and Africa have a much higher incidence of cervical cancer than White women (American Cancer Society, 2007a). Immigrant women have a much lower rate of utilization of health services, particularly preventive services than White women (Chavez, Cornelius, & Jones, 1986;Jacobs & Rapoport, 2003). These trends are also observed in preventive health care-seeking and are especially evident among immigrant women who are unmarried, do not have access to health insurance or contact with physicians and family planning practitioners after migration, lack accurate cervical cancer information, and have diverse religious and cultural ideologies (Green, Freund, Posner, & David, 2005;Scarinci, Beech, Kovach, & Bailey, 2003;Taylor et al, 2002;Taylor et al, 1999;Taylor et al, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%